IDENTIFIKASI LAPISAN AKUIFER AIR TANAH DENGAN MENGGUNAKAN METODE GEOELEKTRISITAS KONFIGURASI SCHLUMBERGER DI TAMAN SALMA SHOFA SAMARINDA, KALIMANTAN TIMUR - Rezky, Bayu; Mandang, Idris (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
The geoelectric method is one of the geophysical methods. It studies the electrical properties on earth and detects on the surface of the earth. In this case includes the measurement of potential, currents and electromagnetic fields that occur either naturally or due to injection of current into the earth. This research was conducted at Salma Shofa garden. Geographically, the location of Salma Shofa Garden is located at 117° 12' 43.0326